Show your true colours: can the use of colour aid memory for Chinese speakers’ English L2 vocabulary acquisition? - Leung, KP (2022)
The purpose of this study is to examine the use of colours in aiding memory for English L2 vocabulary acquisition. ‘4-colour memory’ is an innovative vocabulary strategy that encourages language learners to have self-directed learning. By reviewing their word knowledge, learners use a colour-coding system to highlight words in a colour, indicating how well they know the word. For example, blue for full knowledge of the word, green for fundamental knowledge, yellow for only impression but no knowledge, and red for no knowledge at all. This study took the first step to empirically test this method and see if it helped learners to memorise words better. 99 secondary school students in Hong Kong participated in this study and they were assigned into 3 groups. During the reading comprehension task, the ‘multiple-colour’ group used the ‘4-colour memory’ approach to highlight words according to their familiarity with the word, the ‘single-colour’ group only used the colour yellow, and the ‘no-colour’ group did not use any colours. After analysing the results from pre-tests and post-tests, participants improved from the pre-test to the post-test in general. However, there were no statistical differences between the learning session and conditions so it could not be discerned whether colours helped the participants to learn. Based on the observations of participants’ performance in the 3 different groups, this paper discusses some practical pedagogical implications for educators to consider. Future research avenues are also discussed with the hope that learners can grow more independent in L2 vocabulary learning.